2023
DOI: 10.3390/geriatrics8030049
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Potentially Inappropriate Medications and Polypharmacy on 3-Month Hospital Readmission among Older Patients: A Retrospective Cohort Study from Malaysia

Abstract: Introduction: Potentially inappropriate medications (PIMs) use and polypharmacy are two issues that are commonly encountered among older people. They are associated with several negative outcomes including adverse drug reactions and medication-related hospitalization. There are insufficient studies regarding the impact of both PIMs and polypharmacy on hospital readmission, especially in Malaysia. Aim: To investigate the possible association between polypharmacy and prescribing PIMs at discharge and 3-month hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Consequently, older adults often require a higher number of prescription medications (Gurwitz et al, 2003;Mangoni and Jackson, 2004;Jaul and Barron, 2017). On a global scale, the inappropriate use of medications in this demographic, known as potentially inappropriate medication (PIM) use, poses a significant risk (Akkawi et al, 2023;AlHarkan K et al, 2023). Several studies suggested that PIM use elevates the likelihood of experiencing adverse drug reactions, hospital admissions, emergency room visits, and, in severe cases, mortality.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, older adults often require a higher number of prescription medications (Gurwitz et al, 2003;Mangoni and Jackson, 2004;Jaul and Barron, 2017). On a global scale, the inappropriate use of medications in this demographic, known as potentially inappropriate medication (PIM) use, poses a significant risk (Akkawi et al, 2023;AlHarkan K et al, 2023). Several studies suggested that PIM use elevates the likelihood of experiencing adverse drug reactions, hospital admissions, emergency room visits, and, in severe cases, mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggested that PIM use elevates the likelihood of experiencing adverse drug reactions, hospital admissions, emergency room visits, and, in severe cases, mortality. (Akkawi et al, 2023;AlHarkan K et al, 2023).In a local context, health system in Saudi Arabia is eager to change and improve the citizen health by increasing the life expectancy age to 78 by 2030 according to Saudi Vision 2030 by several programs and initiatives run by Saudi health transformational plan. Such implementation of PIM will improve health services, promoting prevention of health risk, improving quality and efficiency of the current health services towards older adults and eventually will lead to improve the health of Saudi Older adults (Chowdhury et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation